Cover Image, Volume 121, Number 7, July 2020. Issue 7 (31st May 2020) - Won Lee, Gi; Thangavelu, Muthukumar; Joung Choi, Min; Yeong Shin, Eun; Sol Kim, Han; Seon Baek, Jong; Woon Jeong, Young; Eun Song, Jeong; Carlomagno, Cristiano; Miguel Oliveira, Joaquim; Luis Reis, Rui; Khang, Gilson
Abstract : Front Cover : The cover image is based on the RESEARCH ARTICLE Exosome mediated transfer of miRNA‐140 promotes enhanced chondrogenic differentiation of bone marrow stem cells for enhanced cartilage repair and regeneration by Gi Won Lee et al., https://doi.org/10.1002/jcb.29657 .